IOT Based Mind Controlled BOT - Sur, D; Roy, S; Basak, A; Mitra, S; Paul, A; Nayna, S; Chakraborty, A (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IOT) based mind-controlled bot is a software-hardware interface that deals with the interconnection between the hardware and the software. In this work, the hardware components are Arduino, Node Mcu etc. The software interfaces are the NI Instruments LabVIEW, html, and many others. Iot based mind-controlled bot is a total amalgamation of hardware and software. The Electroencephalograph (EEG) signals are sent to the LabVIEW software with the help of Neurosky (mind wave gear) by the Bluetooth Module HC 05. Firstly, EEG signals are differentiated into three types- concentration, meditation and attention. Secondly, it can be further differentiated into alpha, beta and delta signals in order to get more precise values. Since, the Arduino cannot take low values the signals are amplified in the LabVIEW software. From this software, the signals are sent to the Node Mcu which is basically connected to the bot. Here, the concentration has been used in order to pick and drop an object. A web page is also created in the IOT platform with the help of LabVIEW software where four buttons are created to move the total bot. This mechanism which can be used for picking and dropping of an object as an arm using neuro-signal can be very useful for any disabled person as it is acting as an artificial hand.